МАГИЧНИОТ РЕАЛИЗАМ И НЕГОВИТЕ РЕЛАЦИИ СО ЕКСПРЕСИОНИЗМОТ, НАДРЕАЛИЗМОТ И ФАНТАСТИКАТА - Jasmina Mojsieva-Gusheva (Philological Studies, 2019)
This study seeks to peel away the essence of magical realism, by studying its relations with other art movements and areas such as expressionism, surrealism and fantasy. The aim of this study is to provide a theoretical explication of magical realism as a phenomenon, as a style of expression, and as an artistic creation procedure, which first appeared in the German post-expressionist paintings in the twenties of the twentieth century. From there and then, it quickly got distributed through various art forms (literature, theater, film) and traditions (European, Russian, Latin America) and has become one of the most used artistic expressions in the 20th century. In the relationships with the already mentioned art areas, the magical realism’s receptiveness and communicability is emphasized, along with its status of an autonomous stylistic and artistic process, characterized by a new objectification of reality and specific expression. By the help of applied comparative and analytical method, a gradient of the magical realism’s variations is done, conditioned primarily from the contexts in which it appears.